ANALISIS PENGARUH INFORMASI UKURAN PERUSAHAAN, PROCEEDS, FINANCIAL LEVERAGE DAN RETURN ON ASSET TERHADAP PENENTUAN HARGA SAHAM PADA SAAT IPO - Ahmad Kholid; Dyah Fitriani (Jurnal Fokus Manajemen Bisnis, 2013)
This study aims to examine how the influence of financial variables are: total assets, proceeds, Financial leverage, ROA of the company’s stock-market pricing of IPO. Data used in this research is secondary data in the form of a list of manufacturing companies that do an IPO in 2006-2007. Based on the analysis of regression, All independen variable have influence for dependen variable, From the results of the F test showed jointly significant effect on the determination of the share price after listing on the secondary market When viewed in a partial, of the four independent variables there are 2 variables that have a significant effect in determining the offering price that is, total assets, proceeds. And for variable Financial leverage and ROA are not significant in determining the offering. The amount of influence of independent variables to the stock price as the dependent variable 55.3%, and mean 44.7% influenced by other variables not included in this study.